How Knowledge Sharing Influences Patient Health Literacy and Doctor-Patient Trust: Evidence from Chronic disease doctors in China - Lu, R.; Ma, S. (EURAM 2025, 2025)
Objective: Guided by the theory of planned behavior, this study was designed to provide a comprehensive understanding of the formation of chronic disease doctors' behavioral intention and actual behavior of knowledge sharing, and their associations with perceived patient health literacy, and doctor-patient trust. The moderating effect of job effort was also examined. Methods: From March to April 2024, 607 valid questionnaires were collected from chronic disease doctors in 39 public hospitals across 15 Chinese cities. Hypotheses were tested using Mplus 8.3. Results: The findings confirm attitude, subjective norm, and perceived behavioral control as antecedents of behavioral intention to share knowledge. Additionally, it indicates that: 1. Behavioral intention mediates the link between perceived behavioral control and actual behavior of knowledge-sharing. 2. Perceived patient health literacy partially mediates the relationship between actual behavior of knowledge-sharing and doctor-patient trust. 3. Sequential mediation exists from antecedents of behavioral intention to doctor-patient trust via behavioral intention, actual behavior, and perceived patient health literacy. 4. Most importantly, job effort attenuates the positive relationships between behavioral intention and actual behavior of knowledge-sharing and between actual behavior of knowledge-sharing and perceived patient health literacy. Specifically, the above relationships were less significant when doctors reported a higher level of job effort. Conclusion: This empirical study provides theoretical insights into the factors promoting knowledge sharing behavior among chronic disease doctors, and highlights the critical role of job effort on doctors’ actual behavior of knowledge sharing and perceived patient health literacy. It also offers practical guidance for enhancing patient health literacy and improving doctor-patient trust, with management implications for governments, hospitals, doctors, and patients.